PENGARUH KEBOCORAN UMPAN SUSPENSION PREHEATER TERHADAP PERSEN OUTPUT PRODUK STUDI KASUS: PT. SEMEN BATURAJA Tbk - Suryaningsih, Suryaningsih; Safaruddin, Safaruddin (Jurnal Multidisipliner Bharasumba, 2023)
Leakage in the dust transport unit to the suspension preheater is very important to note, because if the leak is in the percentage of more than 15% with a percentage of product output <55% then the operation must be stopped, because the product produced does not match the amount of raw material used. In this case, the output percentage is 65.29% and the total dust loss is 15%. In this condition the factory is still feasible to operate but with a note through extra supervision. Because if the percentage of product output continues to decrease, the operating conditions such as the amount of heat and pressure used will not be appropriate, and the resulting product (clinker) is of poor quality.